Beijing turns to the seas. Combining assertive postures with cooperation - Albana, Alessandro (Asia in World Politics: Past, Present, and Future, 2021)
China’s effort to build itself up into a maritime superpower has drawn scholars’ attention. Questions arise whether the Chinese maritime turn can be considered in terms of potential destabilization of the maritime border in the Western Pacific and Indian Ocean region, or rather, as a contributor to maintaining such an order. Those who believe that China’s maritime rise represents a destabilizing force, point at Beijing’s assertive posture in the East and South China seas. Other scholars argue, that Chinese navy (PLAN) has taken part in humanitarian assistance, disaster relief (HA/DR) and anti-piracy missions in the Indo-Pacific region, contributing to the international maritime cooperation. State-of-the-art analyses have focused either on China’s assertiveness, chiefly in regional seas, or on Beijing’s difficulties to catching up with a blue-water navy status in a global scenario. Rather than assuming China’s maritime projection as a uniform pattern, this study empasizes that Beijing pursues a twofold strategy. On regional waters, where its navy is capable of exercising effective military might, China operates assertively and does not seek multilateral cooperation. On the high seas, where PLAN’s forays suffer from weaker preparedness and training, Beijing has joined the international community in maintaining the world order. China pursued naval diplomacy efforts, as demonstrated by its participation in anti-piracy missions in the Gulf of Aden since 2008 and its contribution to numerous HA/DR initiatives. China’s regional assertiveness and its global cooperative posture reinforce Beijing’s maritime projection.